Environmentally Sound Community Empowerment - Dimas Rahman Rizqian; Muslihudin; Arizal Mutahir (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
This research aims to explain the empowerment of environmentally conscious communities through waste management implemented by the Banyumas Regency Government. This study used qualitative research methods. The targets of this research are parties directly related to waste management policies in Banyumas Regency who were selected purposively. Data collection was carried out through observation, interviews and documentation. Data analysis process. Data analysis in this study was carried out using on going analysis (interactive). The results of the study found that the Banyumas community has a waste management capacity that has a cash flow of millions of rupiah. Then, the people of Banyumas have a responsibility to partner with community members in overcoming the waste problem and meeting their daily needs. This is reflected in the operationalization carried out by the community and financed by the community itself.